Ricardo Silva-Santisteban (2018). Escrito en el agua. Tercera edición. Lima, Alastor Editores, 570 pp. - Ventura Vásquez, Williams Nicks (Mercurio Peruano. Revista de Humanidades, 2021)
Ricardo Silva-Santisteban (2018). Escrito en el agua. Tercera edición. Lima, Alastor Editores, 570 pp.